On Medium Frequency Differential Mode Resonance Effects in Electric Machines - Hans Barnklau (IEEE, 2021)
This paper deals with medium frequency resonance effects in electrical machine windings, which can be excited by harmonic components of voltage source converters. The topic is getting more and more relevant with steadily increasing switching frequencies. For squirrel-cage induction machines with form-wound coils an algorithm is presented, which allows the prediction of first machine differential mode resonance frequencies already at design stage. Examples of the experimental model verification and interpretation of resonance frequencies complete the article.